Evaluasi efek samping obat pada pasien rawat inap di Rumah Sakit “X” di Jakarta - Iyan Hardiana; Ivans Panduwiguna; Aji Abdaul Mujaki; Jerry Jerry; Taufani Taufani (STIKes Surya Global Yogyakarta, 2022)
One of the problems related to the use of drugs is the presence of side effects of drugs. Side Effects Drugs are responses to a drug that is detrimental and undesirable and that occur at doses typically used in humans for the prevention, diagnosis, or therapy of diseases or the modification of physiological functions. Side effects in drug administration are unexpected effects that can arise in treatment. This study aims to determine the number of Side Effects of Drug incidences and what drugs cause Side Effects of the Drug on inpatients at